Inhibition of Angiopoietin-Like Protein 3 With a Monoclonal Antibody Reduces Triglycerides in Hypertriglyceridemia. Issue 6 (6th August 2019) - Ahmad, Zahid; Banerjee, Poulabi; Hamon, Sara; Chan, Kuo-Chen; Bouzelmat, Aurelie; Sasiela, William J.; Pordy, Robert; Mellis, Scott; Dansky, Hayes; Gipe, Daniel A.; Dunbar, Richard L.
Abstract : Background: Hypertriglyceridemia is associated with increased cardiovascular risk and may be caused by impaired lipoprotein clearance. Angiopoietin-like protein 3 (ANGPTL3) inhibits lipoprotein lipase activity, increasing triglycerides and other lipids. Evinacumab, an ANGPTL3 inhibitor, reduced triglycerides in healthy human volunteers and in homozygous familial hypercholesterolemic individuals. Results from 2 Phase 1 studies in hypertriglyceridemic subjects are reported here. Methods: Subjects with triglycerides >150 but ⩽450 mg/dL and low-density lipoprotein cholesterol ≥100 mg/dL (n=83 for single ascending dose study [SAD]; n=56 for multiple ascending dose study [MAD]) were randomized 3:1 to evinacumab:placebo. SAD subjects received evinacumab subcutaneously at 75/150/250 mg, or intravenously at 5/10/20 mg/kg, monitored up to day 126. MAD subjects received evinacumab subcutaneously at 150/300/450 mg once weekly, 300/450 mg every 2 weeks, or intravenously at 20 mg/kg once every 4 weeks up to day 56 with 6 months of follow-up. The primary outcomes were incidence and severity of treatment-emergent adverse events. Efficacy analyses included changes in triglycerides and other lipids over time. Results: In the SAD, 32 (51.6%) versus 9 (42.9%) subjects on evinacumab versus placebo reported treatment-emergent adverse events. In the MAD, 21 (67.7%) versus 9 (75.0%) subjects on subcutaneously evinacumab versus placebo and 6 (85.7%) versus 1 (50.0%) on intravenously evinacumab versus placebo reported treatment-emergent adverse events. No serious treatment-emergent adverse events or events leading to death or treatment discontinuation were reported. Elevations in alanine aminotransferase (7 [11.3%] SAD), aspartate aminotransferase (4 [6.5%] SAD), and creatinine phosphokinase (2 [3.2%) SAD, 1 [14.3%] MAD) were observed with evinacumab (none in the placebo groups), which were single elevations and were not dose-related. Dose-dependent reductions in triglycerides were observed in both studies, with maximum reduction of 76.9% at day 3 with 10 mg/kg intravenously ( P <0.0001) in the SAD and of 83.1% at day 2 with 20 mg/kg intravenously once every 4 weeks ( P =0.0003) in the MAD. Significant reductions in other lipids were observed with most evinacumab doses versus placebo. Conclusion: Evinacumab was well-tolerated in 2 Phase 1 studies. Lipid changes in hypertriglyceridemic subjects were similar to those observed with ANGPTL3 loss-of-function mutations. Because the latter is associated with reduced cardiovascular risk, ANGPTL3 inhibition may improve clinical outcomes. Clinical Trial Registration: https://www.clinicaltrials.gov . Unique identifiers: NCT01749878 and NCT02107872. Abstract : Supplemental Digital Content is available in the text.